QUALITY OF ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN KOTA BARU VILLAGE, NEGRI AGUNG DISTRICT, WAYKANAN REGENCY - Sindi Sintia; Khairudin (ZILLZELL MEDIA PRIMA, 2024)
The accountability of village fund management in Kota Baru has not complied with the provisions of Pamengeri No113 of 2014. This research aims to assess the level of accountability of financial management of Kota Baru Village, Negri Agung District, Waykanan Regency. The research method applied is qualitative, where direct interviews are conducted with the treasurer, secretary, and village head. The results of the research prove that the principle of accountability in village fund management has been implemented well, reflecting positive financial governance. In terms of planning, implementation, and accountability. It is hoped that the application of this accountability principle can be improved in the future through increasing understanding of the village apparatus by participating in socialization and also improving the quality of education.